Oligoprogressive non-small-cell lung cancer under treatment with PD-(L)1 inhibitors - Rheinheimer, Stephan; Heußel, Claus Peter; Mayer, Philipp; Bozorgmehr, Farastuk; Winter, Hauke; Herth, Felix; Muley, Thomas; Liersch, Stephan; Bischoff, Helge; Kriegsmann, Mark; El-Shafie, Rami; Stenzinger, Albrecht; et al. (Cancers, 2020)
Oligoprogression (OPD) of non-small-cell lung cancer (NSCLC) occurs in approximately half of patients under targeted compounds (TKI) and facilitates use of regional therapies that can prolong survival. In order to characterize OPD in immunotherapy (IO)-treated NSCLC, we analyzed the failure pattern under PD-1/PD-L1 inhibitors (n = 297) or chemoimmunotherapy (n = 75). Under IO monotherapy, OPD was more frequent (20% vs. 10%, p < 0.05), occurred later (median 11 vs. 5 months, p < 0.01), affected fewer sites (mean 1.1 vs. 1.5, p < 0.05), and involved fewer lesions (1.4 vs. 2.3, p < 0.05) in the first compared to later lines. Lymph nodes (42%, mainly mediastinal) and the brain (39%) were mostly affected, followed by the lung (24%) and other organs. Compared to multifocal progression, OPD occurred later (11 vs. 4 months, p < 0.001) and was associated with longer survival (26 vs. 13 months, p < 0.001) and higher tumor PD-L1 expression (p < 0.001). Chemoimmunotherapy showed a similar incidence of OPD as IO monotherapy (13% vs. 11% at 2 years). Local treatments were applied regularly for brain but only in 50% for extracranial lesions. Thus, NSCLC oligoprogression is less common under IO than under TKI, but also favorable. Since its frequency drops later in the disease, regular restaging and multidisciplinary evaluation are essential in order to exploit the full therapeutic potential.
Gesehen am 17.07.2020